2013
DOI: 10.1161/circulationaha.112.154757
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letter Regarding Article, “Histone Deacetylation Inhibition in Pulmonary Hypertension: Therapeutic Potential of Valproic Acid and Suberoylanilide Hydroxamic Acid”

Abstract: In their letter, Bogaard et al appreciate that HDAC inhibitors "may mitigate pulmonary vascular remodeling through effects on lung endothelial cells or vascular smooth muscle cells" 1,2 but are concerned about the possibility that "HDAC inhibitors threaten the heart's adaptive response to pressure overload." These concerns, which were addressed in our articles, 1,2 arise from their own study using trichostatin A, a broad-spectrum HDAC inhibitor, and valproic acid, which is not a broad-spectrum HDAC inhibitor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(127 citation statements)
references
References 5 publications
(6 reference statements)
4
122
1
Order By: Relevance
“…This provides an excellent rationale for the extension into therapeutic interventions in a mouse model of PAH. Indeed, non‐specific histone acetylation modifiers reverse the development of PAH and both right and left ventricular function in several animal models …”
Section: Discussionmentioning
confidence: 99%
“…This provides an excellent rationale for the extension into therapeutic interventions in a mouse model of PAH. Indeed, non‐specific histone acetylation modifiers reverse the development of PAH and both right and left ventricular function in several animal models …”
Section: Discussionmentioning
confidence: 99%
“…Whether chronic hypoxia, or any stimulus for that matter, modulates intracellular signaling patterns to change fibroblast phenotype and there is a recruitment and expansion of a unique AF subset remain to be elucidated. Emerging evidence suggests that the stable changes in the proliferative and inflammatory phenotype of AF from the pulmonary hypertensive vessel wall are due to increases in HDAC activity and thus may be considered to have undergone epigenetic modification (20, 21). …”
Section: Adventitial Fibroblast - a “Sentinel Cell”mentioning
confidence: 99%
“…The alteration of acetylation is closely involved in a variety of pathological diseases including neurological disorders, cancers, and cardiovascular, respiratory, and inflammatory diseases [7,28]. So far, several studies have shown that HDAC inhibitors decrease hypertrophy, inflammation, fibrosis, hypertension, proliferation, and atrial fibrillation [11,15,17,20,36,42,43]. Recently, we and a McKinsey research group have reported that HDAC6 is associated with chronic hypertension in certain animal models [15,21].…”
Section: Introductionmentioning
confidence: 99%